2004
DOI: 10.1159/000076337
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxyisovalerylshikonin and Cisplatin Act Synergistically to Inhibit Growth and to Induce Apoptosis of Human Lung Cancer DMS114 Cells via a Tyrosine Kinase-Dependent Pathway

Abstract: β-Hydroxyisovalerylshikonin (β-HIVS) and cisplatin (CDDP) had a synergistic growth-inhibitory effect on cultured human small-cell lung carcinoma DMS114 cells, as well as on human leukemia U937 and epidermoid carcinoma A431 cells, while β-HIVS and CDDP alone at the same respective concentrations had little effect. Growth inhibition was accompanied by induction of apoptosis, as determined by an ELISA for the detection of cell death and the TUNEL assay. Using phosphotyrosine-specific antibodies (PY20), we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The results of the present study indicate that β-HiVS is highly effective in suppressing the growth of β choriocarcinoma cells at a low concentration (10 -6 -10 -5 M), in agreement with the findings of previous reports (5)(6)(7)(8). The marked arrest of cancer cells in the G 0 /G 1 phase of the cell cycle is likely to account for this effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study indicate that β-HiVS is highly effective in suppressing the growth of β choriocarcinoma cells at a low concentration (10 -6 -10 -5 M), in agreement with the findings of previous reports (5)(6)(7)(8). The marked arrest of cancer cells in the G 0 /G 1 phase of the cell cycle is likely to account for this effect.…”
Section: Discussionsupporting
confidence: 93%
“…1), one of the derivatives of shikonin, is an aTP non-competitive inhibitor of the protein-tyrosine kinases (5), and has the strongest apoptosis-inducing activity of the shikonin derivatives (6). β-HiVS has been demonstrated to inhibit the proliferation and induce the apoptosis of tumor cells, including leukaemia (6,7), malignant melanoma (6), lung cancer (5,7,8), endometrial and ovarian cancer (9) cells, at ic 50 values ranging between 10 -6 and 10 -8 M. However, β-HiVS alone was shown to have no significant effect on the growth of human epidermoid carcinoma a431 cells at a concentration of 10 -5 M (10). The effect of β-HiVS on choriocarcinoma cells has not previously been described.…”
Section: Introductionmentioning
confidence: 99%
“…This is actually better than activities for cisplatin in these cell lines as measured by us and reported in literature, i.e. IC 50 = 3.08 µM (A-498; 120 h) [19] and 6.41 µM (U-937; 48 h) [20]. The distinctly different cytotoxicities of the melophlin couples B/C and R/Q are remarkable, given their great structural similarity.…”
Section: Biological Evaluationsupporting
confidence: 42%
“…2 10 ± 1.0 9.0 ± 0.6 6.1 ± 0. b Also see ref [19]. c Not measured; ref [20] quotes an IC 50 = 6.41 µM for an MTT assay (48 h). …”
Section: Agar Diffusion Assaysmentioning
confidence: 99%
“…Hashimoto et al, 2002 found that beta-HIVS was able to induce cell death more efficiently in DMS114 and NCI-H522 lung cancer cells [6]. Xu et al, 2004 also presented the similar results [18]. Masuda and his study group had previously validated the effects of beta-HIVS on U937 and HL-60 leukemia cells and found both two kinds of cell lines all suffered from apoptosis when treated with 10 -6 M beta-HIVS [14].…”
Section: Discussionmentioning
confidence: 68%